Effet de la mycorhization sur des systèmes enzymatiques de défense chez le maïs (Zea mays L.). - Verreault, Catherine. (University of Ottawa (Canada), 1999)
Many studies have shown that mycorrhizal symbiosis can induce synthesis of phenolic compounds associated with plant protection against environmental stress factors. This protection could be beneficial for the plant, especially at early stages of mycorrhizal colonization. Therefore, it is hypothesized that mycorrhizal symbiosis induces changes in phenolic synthesis in the early stages of corn growth. Phenolic synthesis was studied by analyzing the activity of phenylalanine ammonia-lyase and peroxidase and determining the concentration of phenolic compounds by spectrophotometry and HPLC. Two corn cultivars, Pioneer 3737 and Pride K127, were grown in the greenhouse, colonized or not with Glomus intraradices Schenck and Smith (Premier Tech). Plants were harvested from the second to the tenth week of growth. Mycorrhizal colonization was around 20% for both maize cultivars Mycorrhizae tend to enhance PAL activity in corn roots at the fifth week. Peroxidase activity was significantly higher in mycorrhizal plants for all weeks studied. The concentrations of proteins and soluble phenolics were influenced by cultivars and mycorrhizae at certain weeks. Hydroxamic acid concentration was not different in mycorrhizal and non-mycorrhizal corn roots of Pioneer 3737. The low root colonization might have influenced the lack of differences between mycorrhizal and control plants. Mycorrhizal symbiosis seemed to induce an enzymatic defense response in maize at early stages of growth and colonization.
Keywords: Agriculture, Agronomy.